REKONSTRUKSI MODEL EVALUASI PEMBELAJARAN HOLISTIK BERBASIS NILAI DALAM PENDIDIKAN MENENGAH: STUDI PADA SMA DI KABUPATEN SIKKA - Kanisius Bhila; Losianus Harjon; Petrus Dewantara Brliant Egus; Yosef Adrianus Lado Hurint; Stefania Oliva Kago (STKIP Subang, 2026)
The development of educational systems continues to experience significant transformation, particularly in the aspect of learning evaluation, which is no longer solely oriented toward academic achievement but also toward character formation and spiritual values. Schools as modern educational institutions are required to develop comprehensive and adaptive evaluation systems in response to contemporary challenges. One concrete form of this transformation is the implementation of a holistic learning evaluation model integrating diagnostic, formative, and summative assessments with character value reinforcement. The assumption that evaluation is not merely a measurement tool but a reflective instrument to develop students’ overall potential requires teachers and schools to establish objective, sustainable, and value-based assessment systems. Based on this assumption, strengthening teacher professionalism and integrating academic, affective, and spiritual aspects into evaluation becomes an essential need in secondary education. This is particularly important for schools committed to forming young generations who are intellectually competent as well as morally and socially mature. This study employed a descriptive qualitative approach using field research methods, including interviews, observations, and documentation conducted in several senior high schools in Sikka Regency, Maumere. It is expected that this research will contribute conceptually to the development of a value-based holistic learning evaluation model capable of improving educational quality and teacher professionalism sustainably.